The International Court of Justice’s Jurisdiction to Review Its Judgments: Understanding Article 61 of the ICJ Statute in Light of Its Drafting History - Jamil Ddamulira Mujuzi (Universitas Negeri Semarang, 2025)
Judgments of the ICJ are final and not subject to appeal. However, Article 61 of the ICJ Statute empowers the ICJ to review its judgments. The ICJ replaced the Permanent Court of International Justice (PCIJ). Article 61 of the PCIJ Statute (1920) empowered the PCIL to review its decisions. When the PCIJ ceased to exist, Article 61 of its Statute was reproduced, almost verbatim, as Article 61 of the ICJ Statute. In this article, the author illustrates the drafting histories Articles 61 of the PCIJ (1920 – 1921) and ICJ (1945) respectively. The PCIJ did not invoke Article 61 of its Statute. The ICJ has so far invoked Article 61 in three judgments. It is illustrated that although the ICJ has not referred to the drafting history of Article 61 in its judgments, its interpretation of Article 61 is substantially consistent with its drafting history. The drafting history of Article 61 suggests that the first criterion that the Court is supposed to assess before deciding whether to exercise jurisdiction is whether the review application has been filed within the stipulated time. If the answer to this question is in the negative, the court should dismiss the application summarily and not discuss the other grounds of admissibility. However, practice from the Court shows that it has not followed this approach. It is also argued that the Court can invoke its inherent jurisdiction to extend the deadline for filing of review applications although the Statute and the Rules are silent on that issue.